2002
DOI: 10.1155/s0161171202106028
|View full text |Cite
|
Sign up to set email alerts
|

A quantum field theoretical representation of Euler‐Zagier sums

Abstract: We establish a novel representation of arbitrary Euler-Zagier sums in terms of weighted vacuum graphs. This representation uses a toy quantum field theory with infinitely many propagators and interaction vertices. The propagators involve Bernoulli polynomials and Clausen functions to arbitrary orders. The Feynman integrals of this model can be decomposed in terms of a vertex algebra whose structure we investigate. We derive a large class of relations between multiple zeta values, of arbitrary lengths and weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…[16]. Let us note that the Drinfeld's associator is also related to multiple zeta values in a linear way [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16]. Let us note that the Drinfeld's associator is also related to multiple zeta values in a linear way [17].…”
Section: Introductionmentioning
confidence: 99%
“…These identities can be derived using the reccurent relations (4.1), (4.5),..., (4.7) of ref. [16]. Let us note that the Drinfeld's associator is also related to multiple zeta values in a linear way [17].…”
Section: Introductionmentioning
confidence: 99%
“…Starting from the four-point case, the use of (39) does not immediately lead to integrals that can all be done just by applying the completeness relation (such integrals are called 'chain integrals'), but it can be shown that it is always possible to achieve a complete reduction to chain integrals using an integration-by-parts algorithm that was initially developed for a somewhat different purpose [12].…”
Section: Bernoulli Numbers and Polynomials In The Worldline Formalismmentioning
confidence: 99%
“…In [69] two of the authors along these lines constructed a worldline QFT geared towards the derivation of identities between multiple zeta values, defined by…”
mentioning
confidence: 99%